Analysis of Autogate Services at I Gusti Ngurah Rai International Airport by the Class I Special Immigration Office TPI Ngurah Rai - Dharma Yudha Satria; Ida Ayu Putu Sri Widnyani; Gede Wirata (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Investment plays a crucial role in driving economic growth and stability, especially In an era of globalization with high international mobility, such as in Indonesia, international airports serve as key gateways to global connectivity and critical centers for immigration services. Modernizing Indonesia's aviation sector, particularly through digitalization and the implementation of technologies such as autogates at international airports, aims to improve the effectiveness, efficiency, and accuracy of immigration services and reduce passenger queues. This innovation aligns with the principles of good governance and smart mobility, with the integration of biometrics and facial recognition for rapid verification. However, autogates still have limitations in detecting non-documentary aspects and assessing behavior, so manual inspections and human oversight remain crucial as complements to maintain national security and sovereignty. For example, at I Gusti Ngurah Rai International Airport, autogates expedite the process but have not yet fully replaced human oversight. Other challenges include infrastructure readiness, human resource competency, and data security, which must be addressed to ensure innovative, efficient, secure, and user-friendly public services, supporting the bureaucratic reform agenda and the quality of future immigration services in Indonesia. Using a descriptive-analytical approach, this study aims to provide a comprehensive overview of the legal and regulatory challenges faced, as well as strategic recommendations for analyzing autogate services at I Gusti Ngurah Rai International Airport by the Class I immigration office specifically for the Ngurah Rai International Airport (TPI). Keywords: Autogate, Immigration, Airport